Analysis of the Basic English Proficiency of Prospective University Students Based on Diagnostic Test Results - Sulistyoadi Jokosaharjo; Ni Luh Komang Julyanti Paramita Sari; Ni Nyoman Nidya Trianingrum (JURNAL PENDIDIKAN BAHASA, 2026)
This study aims to analyze the basic English proficiency of prospective university students through a multiple-choice test administered during the first batch of the admission process at Triatma Mulya University involving a total of 160 prospective students. The instrument used in this study was a multiple-choice diagnostic English test focusing on basic grammar, vocabulary comprehension, and communication expressions. Therefore, the test was not intended to measure complete English proficiency, but to identify students’ initial basic English competence for course design purpose. The study employed a descriptive mixed-method design by categorizing the test items into 10 language components. The findings show that students perform well in communication expressions and relatively well in simple present and past tense, but having difficulties in conditional sentences, subject-verb agreement, verb forms, and complex sentence construction. These findings indicate that an elementary English course should not only repeat general grammar explanations, but also provide communicative drills and contextualized practice.